Stone soup : an old tale - Brown, Marcia (New York : Atheneum Books for Young Readers, 1975)
When three hungry soldiers come to a town where all the food has been hidden, they set out to make soup of water and stones, and all the town enjoys a feast.
Caldecott Medal/Honor.
Elem. School Library Collection.
Wilson's Children.
Book Links (A.L.A.), November 1997.
Child Study Children's Book Committee, December 2000.
Elem. School Library Collection, June 2000.
Keywords: Folklore -- France; Folklore -- France